Selecting Judges in Poland and Germany: Challenges to the Rule of law in Europe and Propositions for a new Approach to Judicial Legitimacy. Issue 4 (1st July 2018) - Sanders, Anne; von Danwitz, Luc
Abstract : The recent reforms of the Polish Judiciary have sparked a lively debate in Europe on the importance of judicial independence. This Article deals with the new Polish system of selecting and appointing judges and critically assesses it in the light of European standards for judicial appointments. It then compares the new Polish system to the German system of selecting judges, which has been advanced as a point of reference for the reform by the Polish government. Finally, the Article reconsiders and challenges some of the established concepts of German constitutional law as to the selection of judges and judicial legitimacy. The Article was closed on September 2, 2017 and accepted for publication. Subsequent developments could be included until March 15, 2018. The authors would like to thank Judge Thomas Guddat and the Deutsch-Polnische Richtervereinigung (Association of German and Polish Judges) for providing valuable details on the reforms in Poland.